1997
DOI: 10.1002/(sici)1096-9071(199708)52:4<349::aid-jmv1>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

RT-PCR based diagnosis and molecular characterisation of mumps viruses derived from clinical specimens collected during the 1996 mumps outbreak in Portugal

Abstract: Clinical specimens collected during an outbreak of mumps were characterised by RT-PCR, nested PCR, and nucleotide sequencing. Mumps virus was positively identified in 12/21(57%) saliva, 9/21(43%), throat and 1/33(3%) urine specimens and further sequence comparison revealed that at least six strains of viruses, which differed from 0-9.43% at the nucleotide levels, were cocirculating during the epidemic. However, phylogenetic analysis showed that these viruses grouped with two previously identified lineages whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 10 publications
2
33
0
Order By: Relevance
“…Afzal et al reported a similar observation from an investigation of an outbreak in Portugal in vaccinated individuals (1). Of the 31 urine samples evaluated by Afzal et al, only one was positive for MuV RNA (3%) (1).…”
Section: Discussionsupporting
confidence: 63%
“…Afzal et al reported a similar observation from an investigation of an outbreak in Portugal in vaccinated individuals (1). Of the 31 urine samples evaluated by Afzal et al, only one was positive for MuV RNA (3%) (1).…”
Section: Discussionsupporting
confidence: 63%
“…Several MuV genotypes exhibit a differential geographical distribution. For instance, genotypes A, C, D, E, and H are mainly observed in the Western Hemisphere (1,2,13,34), whereas genotypes B, F, and I are solely detected in Asia (16,28,30,42). Some studies have reported the potential associations between genotypes C, D, H, I, or J and neuropathogenicity (28,35,36,38).…”
mentioning
confidence: 99%
“…Thus, mumps vaccination is part of the regular immunization schedule of many countries, usually along with the measles and rubella vaccination (i.e., the MMR vaccine) in a single formulation. However, in contrast to rubella and measles, secondary vaccine failure frequently allows MV circulation within highly immunized populations (1,5,8,24,36). The use of a poorly immunogenic genotype A strain called Rubini has been proposed as a cause of these major failures, although the occurrence of mumps in patients immunized with other vaccine strains has also been described (26).…”
mentioning
confidence: 99%